PENGARUH UPAH DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. DARMASINDO INTIKARET MEDAN - Jimmy Andreas; Thomas Sumarsan Goh; Errie Margery (STIE-PMCI, 2020)
Abstract. PT.Darmasindo Intikaret, Medan is a company engaged in the rubber industry that produces semi-finished goods in the form of rubber latex. There is a problem in productivity at PT.Darmasindo Inti Karet where the output results are not as planned. The wage problem that occurs in production division is the provision of wages based on working hours, but does not make a difference in the amount of wages given per hour on national holidays, or at night. The problem of incentives is the promise of giving incentives that are not kept. The company demands the search for sap for raw materials in large quantities and promises to provide incentives to employees.The population in this study were 120 people. The sample in this study amounted to 120 people. Simultaneous hypothesis test results show that wages and incentives have a significant effect on the work productivity of employees of PT.Darmasindo Intikaret, Medan. The results of the partial hypothesis test indicate that each wage and incentive have a significant effect on the work productivity of PT.Darmasindo Intikaret's employees, Medan.Â Â Keywords: Wages, Incentives, Employee Work Productivity.